Mengungkap Permasalahan Pembiayaan Sistem Bagi Hasil dan Islamisasi Teori Keagenan - Ahmad Roziq (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2020)
This study aims to reveal the problem of the profit-sharing system and the solution to the problem. This research uses a qualitative approach and a kasyif analysis. A qualitative approach is used to reveal empirically to find solutions to the problem of profit-sharing system financing. Meanwhile, the kasyif approach is used to analyze the problems and financing solutions for the profit-sharing system based on the perspective of Islamic law. This study uses a case of implementation of profit-sharing systems in Islamic banking. The results of the study concluded that it is necessary to internalize the values ​​of sharia (Islamic sharia ethics) in agency theory or it is necessary to reconstruct agency theory into "sharia agency theory" so that it is more appropriate in explaining agency problems in the production sharing system financing contract.